KAMPANYE KONSERVASI DANAU SENTANI - Henderina J. Keiluhu; Henderite L. Ohee (JURNAL PENGABDIAN PAPUA, 2021)
Located in Jayapura regency, Sentani lake is the bigest lake in Papua Province with total area 9360 ha and it has maximum depth. Geographycaly, the position of this lake is 70-90 m above sea level at coordinate 2°33’ - 2°41’ S, 140°38’ – 140°38’ E. Sentani lake is the main producer of freshwater fish in Jayapura Regency and it support the livelihood of local people especially the local fishermen. The change of habitat and biota of Sentani lake mainly due to the activities of people living around. One of the bigest threat for this lake is habitat break down and exotic species introduction.  As a consequence, recently Sentani lake has becoming the most threatean freashwater ecosystem. The aim of this activity was to  raised the awarness of citizen regarding the important of sentani lake through conservation. Seminar and questionaire are methods use for the activity. The citizen target was young age (PAM and PAR) at local church (GKI Siloam Waena, Jayapura). The result of this activity shown that only 41,3% of PAR and 40,45% of PAM (respondents) has understanding the important of lake conservation. However, after the activity their understanding is increased to 71,8% and 65,91% for PAR and PAM respectively.Keywords: Sentani lake, Jayapura, freshwater ecosystem, freshwater fish